Massacre at Cavett's Station : Frontier Tennessee during the Cherokee Wars - Faulkner, Charles H. (Book collections on Project MUSE., 2013)
In the late 1700s, as white settlers spilled across the Appalachian Mountains, claiming Cherokee and Creek lands for their own, tensions between Native Americans and pioneers reached a boiling point. Land disputes stemming from the 1791 Treaty of Holston went unresolved, and Knoxville settlers attacked a Cherokee negotiating party led by Chief Hanging Maw resulting in the wounding of the chief and his wife and the death of several Indians. In retaliation, on September 25, 1793, nearly one thousand Cherokee and Creek warriors descended undetected on Knoxville to destroy this frontier town. However, feeling they had been discovered, the Indians focused their rage on Cavett's Station, a fortified farmstead of Alexander Cavett and his family located in what is now west Knox County. Violating a truce, the war party murdered thirteen men, women, and children, ensuring the story's status in Tennessee lore. In Massacre at Cavett's Station, noted archaeologist and Tennessee historian Charles Faulkner reveals the true story of the massacre and its aftermath, separating historical fact from pervasive legend. In doing so, Faulkner focuses on the interplay of such early Tennessee stalwarts as John Sevier, James White, and William Blount, and the role each played in the white settlement of east Tennessee while drawing the ire of the Cherokee who continued to lose their homeland in questionable treaties. That enmity produced some of history's notable Cherokee war chiefs including Doublehead, Dragging Canoe, and the notorious Bob Benge, born to a European trader and Cherokee mother, whose red hair and command of English gave him a distinct double identity. But this conflict between the Cherokee and the settlers also produced peace-seeking chiefs such as Hanging Maw and Corn Tassel who helped broker peace on the Tennessee frontier by the end of the 18th century. After only three decades of peaceful co-existence with their white neighbors, the now democratic Cherokee Nation was betrayed and lost the remainder of their homeland in the Trail of Tears. Faulkner combines careful historical research with meticulous archaeological excavations conducted in developed areas of the west Knoxville suburbs to illuminate what happened on that fateful day in 1793. As a result, he answers significant questions about the massacre and seeks to discover the genealogy of the Cavetts and if any family members survived the attack. This book is an important contribution to the study of frontier history and a long-overdue analysis of one of East Tennessee's well-known legends.